Comparison between Real Hospitalization Benefits and Reimbursements from Diagnostic Related Group (DRG) Criteria in HIV Patients - Teera Kolladarungkri; Prapan Cherdchoo-agarm; Dujpratana Pisalsarakij (Siriraj Medical Journal, 2002)
There are an increasing number of patients with the HIV virus in Thailand. The opportunistic infections in these patients are tuberculosis, Cryptococcal meningitis and Pneumocystis cariniiÂ pneumonia. The hospitalization benefits of admission were critical in the process of assessing of the economy of Thai government's budget. The coverage reimbursements from the government are classified according the criteria of the Diagnostic related group or DRG. An attempt to compare the real benefits to Siriraj Hospital and the government reimbursements for treating HIV-related illness was made and will eventually lead to further eventually adjustable reimbursements.